Factors effecting dairy performance in Friesian and Friesian X Iraqi crosses. : Milk yield and lactation period - Al-Ani, L.M.; Al-Rawi, A.A. (Al-Mukhtar Journal of Sciences, 1996)
Least-squares technique was used for analyzing 605 records of Friesian and different grades of Friesian x Iraqi. The cows were maintaned at three farms namely: Abu-Ghraib and Musaiyib Experimental Stations, both owned by the Iraqi Ministery of Agriculture and the College of Agriculturefarm, University of Baghdad. The records included in this study were collected during the period 1950 - 1979. These data were used to evaluate several genetic and nongenetic sources of variation in milk yield. These included sire, genetic group, parity, season of calving, and herd. It was found that sire and parity had highly significant effects on the milk yield (p<0.01), while the effects of the genetic group on milk yield were significant (p<0.05). However, season of calving and herds had no effects. Also, it was found that all these factors had no effects on lactation period. It was also found that 3/4 Friesian was the best in milk production among all genetic groups included in this study. Heritability estimated by paternal half sib intraclass correlation, was 0.21-0.10, 0.02-0.06, for milk yield and lactation period respectively.